Facial and ocular presentations of Carbimazole induced agranulocytosis: A case report (Bangladesh Journal of Medical Science, 2018)
We report a case of 61-year-old lady who presented with signs and symptoms of acute dacryocystitis, preseptal and facial cellulitis secondary to carbimazole induced agranulocytosis. Her condition was complicated by sepsis whereby she was admitted for intravenous antibiotics, subcutaneous Filgrastim administration and surgical intervention.Bangladesh Journal of Medical Science Vol.17(4) 2018 p.678-679